Ability of Vital and Fluorescent Staining in the Differentiation of Schistosoma haematobium Live and Dead Eggs - Forson, Peter O. (Med Sci (Basel), 2019)
This study reports (for the first time) the staining ability of vital (0.4% trypan blue and 1% neutral red) and fluorescent (Hoechst 33258) dyes to differentiate between live and dead Schistosoma haematobium (S. haematobium) eggs in human urine samples. Since S. haematobium egg is important in disease pathology, diagnosis, transmission, and drug development research, it is essential to be able to easily distinguish live eggs from dead ones. Staining is considered a way of enhancing the identification of live and dead eggs. Urine samples from school children were examined for the presence of S. haematobium eggs. Vital and fluorescent dyes were used to stain the samples that contained S. haematobium eggs, after which they were observed using light and fluorescent microscopes, respectively. The Hoechst 33258 provided a good staining outcome for differentiation between live and dead eggs, followed by 0.4% Trypan blue. Regarding the 1% neutral red stain, even though it provided some evidence of which egg was alive or dead, the distinction was not very clear; therefore, it could be useful when used in combination with other stains for egg viability determination. The benefits of this study will include assessing the effect of drugs on S. haematobium eggs in Schistosomiasis research.